Exploring Religious Moderation through Student-Written Flash Fiction - Aflahah Aflahah; Siti Azizah; Eva Nikmatul Rabbianty; Moh. Syafik; Aemy Elyani Mat Zain (Jurusan Tadris Bahasa Indonesia, 2025)
This study examines the integration of religious moderation values through flash fiction written by students. The research design used mixed methods involving 25 students. The data collected consisted of quantitative and qualitative data. Data were collected through a questionnaire related to students' understanding of religious moderation. The results of the initial questionnaire became the basis for teachers in delivering the material to students. After being given the material, students were asked to create a short story containing religious moderation. After completing the story, students were asked to complete a questionnaire containing three questions related to their understanding of religious moderation, its application in the story, and its application in everyday life. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using thematic analysis. The results showed a strong understanding of religious moderation and creative application of it in narratives. Quantitative findings showed an average increase of 20%. These results indicate that flash fiction is a promising educational tool for promoting religious moderation. The initial survey results showed that most students had experienced incidents of intolerance. Data from student-generated stories indicate that the majority of students understand religious moderation as